TEACHERS`S KNOWLEGDE OF THE PHYSICAL EDUCATION UNIVERSITY TEACHERS (Fiep Bulletin - online, 2013)
This study aimed to analyse which teachers' knowledge are adopted by teachers in university. This descriptive and dialectic research was realized by semi-structured interview with three teachers who teach in the Escola Superior de Educacao Fisica da Universidade de Pernambuco. The results show that the teachers knowledge presented according to literature are implicit and explicit inserted in the interviewed teachers speeches. It is suggested a reflection by the teachers about the necessity of think again on the teachers' knowledge which had been transmitted and constructed, in order to promote a qualitative growth in their teaching's formation and performance.
Keywords: Teachers' Knowledge; University; Physical Education.